Enfermedad de Creutzfeldt-Jakob: experiencia de 5 años en un hospital terciaro de Chile - Legua Koc, Sergio; Castillo Torres, Paula; León Mantero, Alfonso; Alvarado Pastenes, Manuel; Godoy Reyes, Gladys; Sáez Méndez, David; Bucarey Tapia, José Luis (Revista Médica de Chile, 2021)
Background: Creutzfeldt-Jakob disease (CJD) is a prion affection that typically produces a rapidly progressive dementia with different neurologic and extra-neurologic manifestations. Aim: To characterize clinical, imaging and electroencephalography findings in patients with a probable CJD. Patients and Methods: A case series study of patients admitted in the Neurology department at a public hospital, between 2014 and 2019. Demographic, clinical, imaging, and electroencephalographic data of patients with probable CJD were analyzed. Results: Seventeen patients aged 63 ± 11 years (53% women) with a probable CJD were gathered. The incidence was 4.7 cases/year per million inhabitants. Twenty four percent of patients had a family history of CJD. The median time between the onset of symptoms and the hospital admission was three months with a survival of four months. The most common clinical manifestations were an amnesic syndrome in 88%, myoclonus in 76%, frontal syndrome and ataxia in 71%. Brain MRI was abnormal in all patients. The preponderant finding was the involvement of the caudate nucleus in 82% of cases. In the EEG, 94% of patients had abnormalities. All had a theta-delta slowing as a base rhythm. The pseudo-periodic pattern was observed in the 29% and status epilepticus in 18%. Conclusions: In this group of patients we observed the heterogeneity of the clinical manifestations of the disease, the frequent imaging and electroencephalographic alterations and the short evolution time leading to death.